A non-randomized pilot study to test the feasibility of developing a frailty scale for pet cats - Elizabeth J. Colleran; Mikel M. Delgado; Yunyi Ren; Alexander J. German; Margaret E. Gruen; Danièlle A. Gunn-Moore; Kathleen Romanowski; Wendy Simpson; Christine Kirnos; Kathleen Keefe Ternes; Judy Karnia; Marybeth Temples; et al. (Frontiers in Veterinary Science)
IntroductionHuman frailty has long been studied and dozens of “frailty scales” have been developed, but equivalent research is more limited in cats. This pilot study aimed to determine the feasibility of recruiting and retaining veterinary practices and owners, collecting study data, and analyzing results about frailty in older cats.MethodsParticipating feline-exclusive practice veterinarians recruited cats aged 11–20 years, of either sex and of any breed. Owners completed a questionnaire about their cat and estimated its frailty. Study veterinarians also estimated the cat's frailty after obtaining a history, conducting a physical examination, and completing a separate questionnaire. The derived variables were used to investigate the following domains of frailty: (1) cognitive function; (2) behavior; (3) activity; (4) body weight; (5) body condition score; (6) muscle condition score; (7) any unexplained changes in weight, cognitive function, or eating behavior; and (8) the number of chronic diseases identified in the cat. Some cats were followed prospectively for 6 months, and mortality during this period was compared with frailty status, as determined by the veterinarian.ResultsHalf (6/12) of the veterinary practices invited to participate successfully recruited 273 owner-cat pairs, with baseline questionnaire results obtained from 189 owners (69%) and veterinarian questionnaires obtained for 210 cats (77%). Of 122 cats having both owner and veterinarian questionnaire results, 45 (37%) were classified as frail by the owner and 51 (42%) by the veterinarian, with 28 (23%) classified as frail on both questionnaires. Of the cats with follow-up data, 13 of the 64 cats (20%) reported by veterinarians to be frail died or were euthanased during the 6-month follow-up, compared with only 1 of 54 cats (2%) that were not reported to be frail (Fisher's exact test P = 0.003).DiscussionDeveloping a brief feline frailty questionnaire (FFQ) was feasible, and the results of such assessments were associated with 6-month mortality. A larger definitive trial should be considered to explore further the (dis)agreement between owners and veterinarians and better understand which frailty signs owners might be missing.